Effects of Mineral Admixtures on the Mechanical Properties of Self Compacting Concrete - A. Al-Jaberia, Layth; A. Waryosha, Waleed; Waleed Abbasb, Zinah (International Journal of Engineering and Technology, 2018)
The objective of this study was to evaluate the properties of Self Compacting Concrete (SCC) produced by locally available materials and the influence of types and dosages of the mineral admixtures on these properties in fresh and hardened phases. To achieve this objective, 7 different mixes of SCC were mixed, tested and evaluated. The results indicate that acceptable SCC mixtures can be created. The type of the mineral admixtures according to its pozzolanic activity has significant effects on the strengths of the studied SCC mixes especially at the 28 and 90 days ages. The excess fineness negatively affects the early age strengths, but it improves the later age strengths. Irregular particle-distribution system and the more dosage of the mineral admixtures negatively affect the strengths of the mixes. The modulus of elasticity of the mixes is slightly lower than that of conventional concretes. Non-destructive tests confirm an inference that there is less heterogeneity of the SCC.Â Â